2011
DOI: 10.1074/jbc.m110.175448
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Input Potentiates the Transforming Growth Factor (TGF)-β1-dependent Signaling to Promote the Export of Inorganic Pyrophosphate by Articular Chondrocyte

Abstract: Transforming growth factor (TGF)-␤1 stimulates extracellular PP i (ePP i ) generation and promotes chondrocalcinosis, which also occurs secondary to hyperparathyroidism-induced hypercalcemia. We previously demonstrated that ANK was upregulated by TGF-␤1 activation of ERK1/2 and Ca 2؉ -dependent protein kinase C (PKC␣). Thus, we investigated mechanisms by which calcium could affect ePP i metabolism, especially its main regulating proteins ANK and PC-1 (plasma cell membrane glycoprotein-1). We stimulated articul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
(56 reference statements)
2
10
0
Order By: Relevance
“…For instance Wnt 5a was previously shown to only activate the non-canonical route of Wnts. However, we and others have demonstrated that this factor activated the canonical pathway as well [23,25]. This latter pathway activation was induced in the presence of LRP1 [25].…”
Section: Y Hu Et Al / Ocn Expression In Oa Osteoblastsmentioning
confidence: 49%
See 1 more Smart Citation
“…For instance Wnt 5a was previously shown to only activate the non-canonical route of Wnts. However, we and others have demonstrated that this factor activated the canonical pathway as well [23,25]. This latter pathway activation was induced in the presence of LRP1 [25].…”
Section: Y Hu Et Al / Ocn Expression In Oa Osteoblastsmentioning
confidence: 49%
“…Therefore, it seems that the amount of Wnt5b produced by OA Obs would not be sufficient to prevent chondrocyte phenotype changes. However, we have also demonstrated that Wnt 5a was responsible for the loss of articular chondrocyte phenotype in the presence of IL-1 [23]. Thus, it could happen that in OA cartilage the mixture of several factors may trigger Wnt5b to be involved in the phenotype change of chondrocytes.…”
Section: Y Hu Et Al / Ocn Expression In Oa Osteoblastsmentioning
confidence: 77%
“…These iCa 2þ variations led to enhanced activation of Ank promoter through ERK1/2 and PKCa pathways activation, and thus promote extracellular inorganic pyrophosphate production 43 . These findings suggest that iCa 2þ changes induced by various stimulations may be involved in promineralizing chondrocyte phenotype induction.…”
Section: Discussionmentioning
confidence: 99%
“…In CH, TGFb1-dependent signaling has been implicated in the elaboration of inorganic pyrophosphate (PPi). 69 On the other hand, exogenous ATP can be directly involved in the generation of PPi, via purinergic receptors. 63,70 In addition, the levels of exogenous ATP are modulated by TGF-b1 signaling, 63 and the responses of CH to ATP were enhanced by TGF-b1.…”
Section: Fig 4 Tissue Morphologymentioning
confidence: 99%